How Not to Get the Word on Architecture: The Effect of Heidegger's Prose on Norberg-Schulz's Theories - Timothy Gould (Oz, 1985)
In the last fifteen years, several notable architectural critics and historians have turned to the work of Martin Heidegger, especially to his essay, "Building Dwelling Thinking".